The attainment of privatisation objectives in two Bulgarian industries - Tony Cox; Graham J. Hooley; Marin A. Marinov; Svetla Trifonova Marinova (Journal for East European Management Studies, 1997)
Privatisation forms an essential part of the progress of Bulgaria towards a free economy. This paper reviews the objectives of privatisation, as exemplified by the UK model, and the conditions necessary for their achievement. It considers the privatisation processes in Bulgaria and their operation in reality in the construction and the beer industries. – – Die Privatisierung bildet einen wesentlichen Teil des Fortschritts Bulgariens auf dem Weg zu einer freien Wirtschaft. Der vorliegende Artikel betrachtet die Ziele der Privatisierung, wie sie durch das 'britische Modell' veranschaulicht werden, und die Bedingungen, die zu ihrer Erreichung notwendig sind. Es wird der Privatisierungsprozeß in Bulgarien und seine Auswirkungen in den Bereichen Bau und Brauereiwesen untersucht.
Keywords: 650